La logica naturale e la concessione - Latos, Agnieszka (Neophilologica, 2017)
This paper discusses the conceptual structure of factual concession, in particular, the nature of its implicit content roughly equating to ‘Normally/usually if p, then not-q’ and the relationship holding between concession and causality. In contrast to many prior accounts of this complex interclausal connection, the discussion here is not based on the traditional system of truth values (i.e. propositional calculus) developed by classical logic, but it seeks to describe concessive relation from the perspective of ‘natural’ human reasoning.